ROLE OF REDOX PROCESSES IN THE INTERACTION OF HETEROTROPHIC MICROORGANISMS OF GOLD-BEARING DEPOSITS WITH COLLOIDAL GOLD - Marakushev S.A.; Balezina T.L.; Kovaleskaya A.N. (My University, 1988)
Microorganisms are effective geochemical agents by virtue of their greater metabolic diversity, and thus their greater biochemical versatility, than plants and animals. The involvement of microorganisms in the solution and reduction of gold has been studied previously with reference to the development of gold-bearing associations. In this paper the authors describe the characteristics of the reaction of bacteria isolated from gold-bearing deposits of Amur Oblast with particles of colloidal gold of various sizes and the bacterial metabolism in these reactions. A system consisting of bacteria and a sol of colloidal gold was used to model a natural biochemical range.